Avaliação do uso de sistema de automação para cultivo de cogumelo Psilocybe cubensis - Tacone, Allan Johnny (Universidade Federal de São Carlos, 2026)
This study evaluated the effectiveness of a low-cost automation system applied to the cultivation of Psilocybe cubensis, comparing it to traditional manual cultivation. Six cultivation greenhouses were built, three automated and three controlled, in which three main parameters were evaluated: dry weight, basidiocarp size, and total number of "individuals". The automated system controlled the temperature by hysteresis (27–29 °C) and performed programmed air exhaust cycles. The results demonstrated that the automated system produced larger mushrooms (Control: 170.64 cm and average: 56.88 cm; Automated: 223.45 cm and average: 74.48 cm), in greater quantity (Control: 15 units; Automated: 20 units); and with greater dry weight (Control: 13.085 g; Automated: 20.393 g). Although the increase in average weight was modest, the significant growth in height and total productivity indicates that temperature and exhaust control aided in the development of the basidiocarps. It is concluded that accessible automated systems can improve the efficiency and standardization of mushroom cultivation, even under simple conditions, reinforcing the potential of Agriculture 4.0 in mushroom farming. Future improvements are suggested, including the automation of humidity control and the integration of CO₂ sensors.
Evaluation of the use of an automation system for the cultivation of Psilocybe cubensis mushrooms.
Keywords: Automação; Cultivo de cogumelos; Agricultura 4.0; Arduino; Automation; Mushroom cultivation; Agriculture 4.0; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS::MICOLOGIA; 2. Fome Zero e Agricultura Sustentável